Value of 18F-fluorocholine PET/CT in predicting response to radical radiotherapy in patients with localized prostate cancer. (September 2021) - Sepulcri, Matteo; Fusella, Marco; Cuppari, Lea; Zorz, Alessandra; Paiusco, Marta; Evangelista, Laura
Highlights: High Choline-PET uptake is predictive of a poor outcome at 3-year follow-up. Primary tumor should be boosted for high semiquantitative data Choline PET. PET-guided dose to the dominant lesion can prolong the free-recurrence time. Abstract: Purpose: This study aims to establish whether metabolic parameters obtainable from FCH PET/CT can predict long-term response to radical radiotherapy (rRT) in patients with localized prostate cancer (PCa). Methods: Drawing on a single-center database, we retrospectively reviewed the pre-treatment FCH PET/CT scans of 50 patients who underwent rRT between 2012 and 2017. Patients were enrolled if they had a follow-up of at least 3 years after rRT. Various metabolic parameters were considered for each PET/CT, including FCH multifocality. rRT was administered to all patients for a total equivalent dose of 76–80 Gy, using a standard or hypofractionated schedule. Patients were classified as disease-free (DF) if their PSA levels after rRT rose by <2 ng/mL vis-à-vis their PSA nadir, or as not disease free (NDF) if their PSA levels rose by more than 2 ng/ml. Results: A multifocal FCH uptake in the prostate gland was identified in 27 patients (54%). At 3-year follow-up, 37 patients (74%) were judged DF, and 13 (26%) were NDF. The SUVmax and SUVmean, and the sum of the two values in all FCH foci in the prostate gland were significantly higher for NDF patients than for DF patients (all p < 0.005). The sum of the TLCKA levels in all FCH foci was likewise significantly higher in patients who were NDF than in those found DF (median 54.5 vs. 29.4; p < 0.05). At univariate analysis, the most of PET-metrics and Gleason Score were predictors of biochemical relapse after 3-year follow-up (all p < 0.05). Conclusion: Higher SUVs seems predict a worse outcome for patients with multifocal intraprostatic lesions who are candidates for rRT.